Development of Reciprocal Teaching-Based Interactive Multimedia to Enhance Students' Learning Outcomes of Database Fundamentals - Subarna, Bambang; Rohendi, Dedi; Rasim, R (Universitas Pendidikan Indonesia, 2022)
Database subjects are one of the basic compulsory subjects for the Computer Engineering and Informatics program. For Software Engineering students, topics such as Data Definition Language (DDL) and Data Manipulation Language (DML) are crucial for understanding advanced lessons. However, learning outcomes have been low due to factors such as suboptimal media, methods, models, and teaching processes. This research aims to design reciprocal teaching-based interactive multimedia to enhance student learning outcomes in DDL and DML materials. The research method used is adapted from the Comprehensive Life Cycle model, with a sample of students from class X-RPL-1 at Bina Wisata Lembang Vocational High School.The results of this study are as follows: 1) An average percentage of 80% was obtained from media experts and 80% from subject matter experts, both categorized as “Very Good”. 2) The use of multimedia improved student learning outcomes, demonstrated by an average score increase from 34 to 73. Furthermore, based on the pretest and posttest results, an average normalized gain (n-gain) of 0.59 was obtained with a criteria of 'Moderate' effectiveness. 3) Students responses to the created multimedia resulted in an average percentage score of 86.41%, categorized as “Very Good”.